Analisis Intervensi Temper Tantrum Pada Anak Berkebutuhan Khusus di Middle Year Programme Al Firdaus Surakarta - Yahya, Nadjibah; Giyoto, Giyoto; Maslamah, Maslamah; Islah, Islah (Riviera Publishing, 2025)
This research aims to determine the interventions carried out by special assistant teachers (GPK) in an inclusive school for children with special needs (ABK). This research is qualitative research with descriptive analysis. The research subjects were all special support teachers, counselors and inclusion coordinators at the Middle Year Program (MYP) Al Firdaus Surakarta. Data collection methods were observation, documents and interviews. The validity of the data is obtained by triangulating the sources. The data analysis method used is interactive data analysis. There are 18 GPK for 33 crew members at MYP Al Firdaus. The results of this research show that there are various interventions, namely physiological, cognitive, interaction and spiritual interventions. Physiological intervention by providing a safe and comfortable place and providing physical touch. Cognitive intervention by providing explanations to crew members and discussing cases that have occurred. Interaction intervention by intervening with friends. Spiritual intervention by reading the Qur'an, reading the kalimah thoyyibah and praying. Not all cases are resolved the same depending on the case and the intensity of the tantrum. Other interventions include being given comfort by having their basic needs met, validating their role and understanding.